PEMANFAATAN CITRA GOOGLE EARTH UNTUK PEMETAAN LAHAN DAN FASILITAS GAMPONG AJEE RAYEUK KECAMATAN INGIN JAYA KABUPATEN ACEH BESAR - Alamsyah Taher; Raiyatul Rizka; Fitriani Yulianti (Geography Education Study Program, Universitas Samudra, 2022)
This study aims as a village atlas that can function as a village profile as well as a spatial and regional planning program in Ajee Rayeuk Village, Want Jaya District, Aceh Besar District. The stages of implementing the activity are (1) preparation which includes field surveys and data collection, (2) data processing which includes data input through the ArGis application, image data cropping, digitization and final layout, (3) final stage which includes map print out, making frames and maps for geuchik gampong. The data analysis technique used in this research is digitization technique. The results showed that from image digitization, Gampong Ajee Rayeuk was divided into 3 hamlets, namely Hamlet Ajee in the east, Dusun Lam Ateuk in the south, Dusun Lam Daya in the west with a total area of ​​52.6 hectares. The land use in Gampong Ajee Rayeuk varies, consisting of residential areas, rice fields, and residential land. The facilities include a grapura, Ajee Rayeuk elementary school, geuchik office, posyandu and meunasah.